2010
DOI: 10.1016/j.febslet.2010.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the carboxy‐terminal Tudor domain from human Coilin

Abstract: a b s t r a c tThe Cajal body is a dynamic eukaryotic nuclear organelle that is known primarily as an organizational center for the assembly of snRNAs involved in transcript splicing. One of the most critical components of the Cajal body is the scaffolding protein, Coilin. Here, we demonstrate by NMR methods that the carboxy-terminal region contains a Tudor domain. The Tudor domain is atypical due to the presence of several unstructured loops, one greater than thirty amino acids in length. Tudor domains have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…4 The conserved C-terminal domain folds into a Tudor domain like structure. 13 Several Tudor domains were found to bind methylated amino acids but direct tests did not show any interaction of coilin Tudor domain with monomethyl-lysine, trimethyl-lysine and dimethyl-arginine. 13 However, the C-terminal domain was shown to interact with Sm proteins, which contain symmetrically dimethylated arginines.…”
Section: Coilin Historymentioning
confidence: 97%
See 1 more Smart Citation
“…4 The conserved C-terminal domain folds into a Tudor domain like structure. 13 Several Tudor domains were found to bind methylated amino acids but direct tests did not show any interaction of coilin Tudor domain with monomethyl-lysine, trimethyl-lysine and dimethyl-arginine. 13 However, the C-terminal domain was shown to interact with Sm proteins, which contain symmetrically dimethylated arginines.…”
Section: Coilin Historymentioning
confidence: 97%
“…13 Several Tudor domains were found to bind methylated amino acids but direct tests did not show any interaction of coilin Tudor domain with monomethyl-lysine, trimethyl-lysine and dimethyl-arginine. 13 However, the C-terminal domain was shown to interact with Sm proteins, which contain symmetrically dimethylated arginines. [14][15][16] Coilin interaction is stronger when Sm proteins are purified from eukaryotic cells rather than bacterially expressed, suggesting that posttranscriptional modifications might play a role in Sm protein-coilin interactions.…”
Section: Coilin Historymentioning
confidence: 97%
“…Little structural information on coilin exists, but a recent study has found that coilin contains a tudor-like domain between aa 460 and 560 [19] (Figure 1). The survivor of motor neuron protein, SMN, which is mutated in most cases of the neurodegenerative disease spinal muscular atrophy [20], also contains a tudor domain.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, binding of U1 and U2 snRNA to coilin are reported to change the protein conformation. This may enhance selfassociation, but a defined binding region within coilin has not been identified 114 (although the C-terminal Tudor domain is predicted to bind nucleic acids 115 ). Thus, many aspects of CB biology are regulated by coilin oligomerization and posttranslational modifications.…”
Section: Pulling Itself Together: Oligomerization and Cajal Body Assementioning
confidence: 99%